PENGARUH FAKTOR LINGKUNGAN TERHADAP DISTRIBUSI SPESIES NYAMUK TERKONFIRMASI VIRUS Japanese encephalitis DI SUMATERA SELATAN - Yahya Yahya; Milana Salim; Santoso Santoso (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
Japanese encephalitis (JE) is one of the zoonotic arbovirus diseases through mosquito bitescauses brain inflammation in humans,mental disability,that can ultimately lead to death. Each year there are about 50,000 cases of JE in Asia with 10,000 deaths. The incidence of Japanese encephalitis in humans has never been reported in South Sumatra. Further analysis to see the effect of temperature, air humidity, wind speed, and weather conditions to the density of mosquito confirmed of JE virus in South Sumatera Province. The method used in this advanced analysis is to submit a data request to the data management of the Research and Development Agency through submission of a data set request. Instruments in this further analysis are Form N-01 (Mosquito Ecosystem), Form N-02 (Human Feed), Form N-03 (Animal Feed), Form N-04 (Animal Baited Trap Net) Vectora Special Research 2015. Analysis data is done by using linear regression test. Temperature is an environmental factor that affects the density of JE positive mosquitoes in theLahat and OKI District. Air humidity and wind speed are environmental factors that only affect mosquito density in OKI,weather conditions only affect the density of mosquitoes in Lahat Regency. The greatest correlation factor with the density of mosquitoes is wind speed(r=0,79).